2010
DOI: 10.1111/j.1365-2133.2010.09776.x
|View full text |Cite
|
Sign up to set email alerts
|

PTCH1 gene haplotype association with basal cell carcinoma after transplantation

Abstract: Haplotypes containing T(1686)-T(3944) alleles were shown to be associated with an increased BCC risk in our study population. These data appear to be of great interest for further investigations in a larger group of transplant individuals. Our results do not support the hypothesis that common polymorphisms in the proximal 5' regulatory region of the PTCH1 gene could represent an important risk factor for BCC after organ transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
0
14
1
Order By: Relevance
“…Numerous studies have reported cases when haplotype-based analysis resulted in detection of an association, while SNP-based analysis either did not yield any significant results or yielded much higher p-values [16-19]. A haplotype-based test may be more powerful than a genotype-based test if haplotypes tag a true causal variant better (although the imputation of untyped SNPs using publicly available reference panels may also be a powerful strategy), or if a SNP-SNP interaction is present within a region.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported cases when haplotype-based analysis resulted in detection of an association, while SNP-based analysis either did not yield any significant results or yielded much higher p-values [16-19]. A haplotype-based test may be more powerful than a genotype-based test if haplotypes tag a true causal variant better (although the imputation of untyped SNPs using publicly available reference panels may also be a powerful strategy), or if a SNP-SNP interaction is present within a region.…”
Section: Introductionmentioning
confidence: 99%
“…Begnini et al, analysed the prevalence of several PTCH polymorphisms, including CGG repeats in the 5′UTR, in immunosuppressed Italian patients who had developed BCC following organ transplantation. They observed the CGG 8 allele in 46% of patients and the CGG 7 allele in 41%; however, this higher frequency was not statistically significant (12). It remains to be determined whether the prevalence of these polymorphisms is more strongly correlated with BCC susceptibility in non-mediterranean, more fair-skinned populations and outside the context of immunosuppression.…”
Section: Resultsmentioning
confidence: 94%
“…rs357564 is a missense variant within PTCH1 and rs1529889 is an intronic variant within ADAMST17 . rs357564 is predicted to be ‘functional’ by the prediction tool FATHMM (Shihab et al , 2015) and was reported to be associated with oral clefts, basal cell carcinoma and ameloblastoma (Begnini et al , 2010; Carter et al , 2010; Farias et al , 2012).…”
Section: Discussionmentioning
confidence: 99%